(untitled) (Bangladesh Journal of Medical Microbiology, 2013)
The suspicion of autoimmune disease primarily starts with clinical symptoms. The ELISA and IIF (indirect immunofluorescence) on HEp-2 cell methods are comparable for detecting ANA in patient with auto immune diseases (AID). 102 patients attending Rheumatology out patient department as new or old cases with provisional diagnosis of SLE, RA, MCTD and other Connective Tissue disorder (CTD) screened for specific autoantibody by ELISA (anti CCP, ANA and anti dsDNA) were subjected to indirect immunofluorescence on HEp-2 cell line. Diagnostic accuracy based on ELISA and indirect immunoflurescence on HEp-2 cell line showed the results of sensitivity, specificity, PPV, NPV, accuracy of ANA were found to be 78.9%, 33.3%, 78.9%, 33.3%. 68% respectively. Sensitivity, specificity, PPV, NPV and the accuracy of anti-dsDNA was 80%, 40%, 80%.40% and 70% respectively. Sensitivity, specificity, PPV, NPV, and the accuracy of anti CCP was found to be 64.3%, 72.2%, 64.3%, 72.2% and 68.8% respectively. The results indicates there is a need for screening all suspected autoimmune patient by indirect immunofluorescence on HEp-2 cell line before going to specific test. DOI: http://dx.doi.org/10.3329/bjmm.v7i1.19315 Bangladesh J Med Microbiol 2013; 07(01): 11-14